Adaptation of the Invasive Plant (Sphagneticola trilobata L. Pruski) to a High Cadmium Environment by Hybridizing With Native Relatives - Gao, Lei; Cai, Minling; Zeng, Lingda; Zhang, Qilei; Zhu, Haoqiang; Gu, Xiaoqian; Peng, Changlian (Frontiers in Plant Science, 2022)
Invasive species can evolve rapidly in the invasion areas to adapt to new habitats. Sphagneticola trilobata L. Pruski, an invasive species, was studied for its tolerance to cadmium (Cd) in the soil and compared with its natural hybrid. From the perspective of photosynthetic physiology, antioxidant characteristics, and leaf hormone levels, the differences between the leaves of the two species before and after Cd treatment were compared. The results showed that the hybrid had stronger tolerance to Cd stress than invasive species. After Cd stress, the indexes of gas-exchange [net photosynthetic rate (Pn), intercellular CO2 concentration (Ci), stomatal conductance (Gs), and transpiration rate (Tr)] of the hybrid was higher than invasive species, while the content of non-enzymatic antioxidants (flavonoids and total phenols) and antioxidant enzyme activities [peroxidase (POD) and superoxide dismutase (SOD)] was lower in hybrid than in invasive species. The changes in the content of plant hormones [auxin (IAA) and abscisic acid (ABA)] under Cd stress showed that hybrid can still maintain growth and prevent leaf senescence. Furthermore, the differences in gene expression between hybrid and invasive species in photosynthetic physiology, the antioxidant capacity of leaves, and endogenous hormone (IAA and ABA) synthesis pathway also showed that hybrid has stronger Cd tolerance than invasive species. This suggests that invasive species will realize the invasion through hybridization with the native relatives to overcome the stress from environmental factors. The study implied that hybridization between invasive species and native relatives is an important way for invasive species to spread in a wider and new environment that invasive species have not experienced in the area of origin.